Pengaplikasian Web Pada Pendaftaran Siswa Baru Menggunakan Model Waterfall Pada Bimbel Cerdas Ceria - Tri Santoso (INFORMAL: Informatics Journal, 2018)
In the world of education, there is always an increase that must be made. The increase is not only in terms of science, but from various sides that support the education world. Every educational institution competes to do this to improve quality in providing education to their students. In this paper, the author takes a case study at Bimbel Cerdas Ceria Tangerang. The registration system at Bimbel Cerdas Ceria still uses a manual system. The system requires prospective students to come directly and do the registration process. Therefore, it is necessary to apply a new student registration web that is able to overcome the problem. The web application is made using the Waterfall method for the analysis stages. With the application of the web, prospective students do not need to come directly to register. Registration confirmation can use e-mail so that no one can confirm the registration. Payments also use ATM so parents don't need to come directly to just make payments.